A Comparative Study Of The Analysis Of The Effect Of Product Quality, Price, And Business Location On Consumer Satisfaction Of The Students Canteen Of Universitas Darussalam Gontor (Study On Dlp And Lawu Caffe) - Saputri, Citra Amanda; Hamidah Tussifah (Islamic Business and Management Journal, 2024)
This study raises problems that occur in the marketing mix, namely product quality, price, business location and student satisfaction as consumers at DLP and Lawu Caffe, Darussalam Gontor University. This study aims to analyze product quality, price, and business location on the satisfaction of UNIDA students after purchasing food products at DLP and Lawu Caffe and comparing the satisfaction of UNIDA students with both of them. This research was conducted at Darussalam Gontor University. This research method uses a quantitative approach and data collection is done by distributing questionnaires with probability sampling techniques, namely simple random sampling to 314 female students of Darussalam Gontor University. The results showed that product quality, price, and business location partially had a positive and significant effect on the satisfaction of UNIDA students as consumers at DLP and Lawu Caffe. Product quality, price, and business location simultaneously together have a positive and significant effect on customer satisfaction with an F count value of DLP 437,123 and F count Lawu Caffe 624,018 with a difference in value of 186,895. With this difference in value, UNIDA students are more satisfied with the product quality, price, and business location of Lawu Caffe compared to DLP.